2022
DOI: 10.3389/fbioe.2022.845042
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapeutic Potential of Mesenchymal Stem Cell-Derived Extracellular Vesicles in Chronic Respiratory Diseases: An Overview of Recent Progress

Abstract: Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) are able to carry genetic and protein goods to mediate the interaction between MSCs and target cells. Recently, more and more researches have focused on the therapeutic role of MSC-EVs in chronic respiratory diseases. In this review, we summarize the cumulative strategies and mechanisms of MSC-EVs in treating chronic respiratory diseases. This review suggests that MSC-EVs may serve as a novel cell-free-based therapy for chronic respiratory diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Although the use of miRNAs as therapeutic drugs is a possibility yet to be verified in clinical trials, at present, more investigations have focused on the therapeutic role of miRNAs derived from extracellular vesicles (EVs). More studies have investigated the use of miRNAs from mesenchymal stem cells (MSC-EVs) from chronic respiratory diseases; these studies have shown promising results [ 178 , 179 , 180 ]. It is also important to highlight that at present not only the miRNAs are under evaluation as potential therapeutic targets, but the non-coding RNAs as long non-coding RNAs (lncRNAs) are also being explored for their possible clinical application in respiratory diseases [ 29 , 30 ], which underline the actual relevance of this type of molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of miRNAs as therapeutic drugs is a possibility yet to be verified in clinical trials, at present, more investigations have focused on the therapeutic role of miRNAs derived from extracellular vesicles (EVs). More studies have investigated the use of miRNAs from mesenchymal stem cells (MSC-EVs) from chronic respiratory diseases; these studies have shown promising results [ 178 , 179 , 180 ]. It is also important to highlight that at present not only the miRNAs are under evaluation as potential therapeutic targets, but the non-coding RNAs as long non-coding RNAs (lncRNAs) are also being explored for their possible clinical application in respiratory diseases [ 29 , 30 ], which underline the actual relevance of this type of molecule.…”
Section: Discussionmentioning
confidence: 99%
“…These properties are due, in part, to the activity of growth factors and cytokines secreted by the MSCs. Recently, researchers revealed that exosomes were responsible for the antifibrotic efficacy of MSCs ( Fujita et al, 2018 ; Ma et al, 2022 ). MSCs derived from bone marrow (BM), adipose tissue (AD), and placenta confirmed that exosomes from MSCs could reduce inflammation by regulating related signaling pathways and polarization, and could also reduce collagen deposition in bleomycin- ( Mansouri et al, 2019 ; Dinh et al, 2020 ; Wan et al, 2020 ), silica- ( Choi et al, 2014 ; Phinney et al, 2015 ; Bandeira et al, 2018 ; Dinh et al, 2020 ), PM2.5- ( Gao et al, 2020 ), and radiation- ( Lei et al, 2020 ) induced PF models and TGF-β stimulated myofibroblasts ( Shentu et al, 2017 ).…”
Section: Exosomes As a Therapeutic Tool For Pulmonary Fibrosismentioning
confidence: 99%
“…Although substantial breakthroughs have been made in the field of MSC-EV-mediated cell-free therapy for DM and diabetic complications, there still exist many challenges that may hinder the clinical application of MSC-EVs: (1) The large-scale production of high-quality MSC-EVs is the major challenge currently. The traditional isolation methods such as ultracentrifugation have several disadvantages including low yield and time-consuming processes, which cannot meet the clinical requirement [ 171 ]. There is an urgent need to develop new separation approaches to rapidly obtain MSC-EVs with high purity.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%